2021
DOI: 10.1016/j.jshs.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness measured with cardiopulmonary exercise testing and mortality in patients with cardiovascular disease: A systematic review and meta-analysis

Abstract: Highlights High cardiorespiratory fitness (CRF) in patients with cardiovascular disease (CVD) is associated with 58% lower all-cause mortality risk and 73% lower cardiovascular mortality risk compared to unfit counterparts. Each 1 metabolic equivalent (1-MET) increase in CRF is associated with a 19% lower CVD mortality risk among patients with CVD. Coronary artery disease patients with high CRF have a 68% lower all-cause mortality risk than their unfit cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 65 publications
0
37
0
4
Order By: Relevance
“…Baseline and post-rehab functional capacity testing, either maximal or submaximal, is a valuable tool in the determination of patient starting points, evaluation of exercise hemodynamics, as well as monitoring improvements gained from cardiac rehabilitation [ 14 ]. Peak or maximal graded exercise testing (GXTs) is the gold standard for the determination of patient functional capacity and allows for the best determination of direct physiological intensity variables, such as HR values [ 10 ]. Abnormal physiological responses to exercise (i.e., ischemia, hypertensive blood pressure) may also be uncovered and limitations may accordingly be placed on patients’ hemodynamic values during exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline and post-rehab functional capacity testing, either maximal or submaximal, is a valuable tool in the determination of patient starting points, evaluation of exercise hemodynamics, as well as monitoring improvements gained from cardiac rehabilitation [ 14 ]. Peak or maximal graded exercise testing (GXTs) is the gold standard for the determination of patient functional capacity and allows for the best determination of direct physiological intensity variables, such as HR values [ 10 ]. Abnormal physiological responses to exercise (i.e., ischemia, hypertensive blood pressure) may also be uncovered and limitations may accordingly be placed on patients’ hemodynamic values during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Functional capacity is also an important indicator of prognosis (e.g., 5-year mortality) among CVD patients [ 9 ]. Specifically, each 1 MET increase in functional capacity confers a 19% reduction in CVD mortality among heart disease patients [ 10 ]. The implementation of safe and progressive exercise prescriptions during enrollment in cardiac rehabilitation is critical to the successful improvement of functional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…It is a comprehensive reflection of the body's exercise capacity ( 4 ), assessed by the quantifiable index of maximum oxygen uptake (VO 2 max). Many studies have shown that CRF is a strong independent predictor of chronic diseases, such as cardiovascular disease ( 5 ) and cancer ( 6 ), and a modifiable risk factor which is influenced by lifestyle and physical activity. Relevant studies have shown that, compared with traditional clinical risk factors for cardiovascular disease, CRF can better predict the health status and possible adverse events ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that exercise-based cardiac rehabilitation (CR) programs reduce mortality rates in patients with CAD [ 1 ]. In this regard, parasympathetic nervous system (PNS) activity and cardiorespiratory fitness (CRF), assessed by heart rate (HR)-based indices (e.g., resting HR, resting HR variability (HRV), and post-exercise HR recovery (HRR)) and maximum oxygen uptake (VO 2 max), respectively, are considered independent predictors of mortality [ 2 , 3 , 4 , 5 , 6 ]. Moreover, Martinez et al [ 7 ] and Medeiros et al [ 8 ] reported an improvement in PNS activity after an exercise-based CR program.…”
Section: Introductionmentioning
confidence: 99%